Association of non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) with 90-day mortality in acute pancreatitis: A MIMIC-IV database analysis - Jiali Xu; Jing Long; Gang Luo; Mingming Deng; Liang Wang (PLoS ONE, 2026)
The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a new composite lipid index. Blood lipid levels are closely associated with the severity of acute pancreatitis (AP), but the relationship between NHHR and mortality in AP patients remains unclear. Therefore, the purpose of this study is to investigate the connection between NHHR and the mortality of patients with AP within 90 days. A total of 454 adult participants with AP from the MIMIC-IV database were categorized into three groups based on their NHHR levels. We employed a multivariate Cox proportional hazards model to assess the relationship between NHHR and 90-day mortality in AP patients. Additionally, we utilized the random forest method to identify the ten most significant risk factors associated with mortality in AP, which was subsequently used to build a prediction model. Out of the patients with AP, 27 died within 90 days. After adjusting for various factors, the hazard ratios for mortality across the tertiles of the NHHR (from the lowest to the highest tertiles: Q1–Q3) were as follows: 1.00 (reference), 1.47 (95% CI: 0.47–4.66), and 4.07 (95% CI: 1.43–11.60). Additionally, the area under the curve (AUC) for our AP mortality prediction model is 0.867 (95% CI: 0.769–0.964). Our findings indicate that a high level of NHHR is closely associated with the mortality of AP, serving as a simple index to predict the prognosis of AP patients.